Analisis Perilaku Belajar Dan Minat Belajar Terhadap Pemahaman Akuntansi Dengan Kecerdasan Intelektual Sebagai Variabel Intervening (Studi Pada Mahasiswa S1 Akuntansi Periode 2017 – 2018 UPN “Veteran” Jawa Timur) - Muhamad Fadel Ardiansyah; Endah Susilowati (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
Higher education institutions are required to not only produce graduates who have mastered abilities in the academic field, but also have technical analytical skills in the field of humanistic skills and professional skills so that they have added value in competing in the world of work. The problem that arises in this research is the understanding of accounting that changes or fluctuates in the Accounting Students of UPN "Veteran" East Java during the period 2017 - 2018. The type of research used is the type of research using quantitative approaches. The results of this study indicate that learning behavior has a significant effect on understanding accounting, learning interest has a significant effect on accounting understanding, learning behavior has a significant effect on intellectual intelligence, learning interest has a significant effect on intellectual intelligence, intellectual intelligence has a significant effect on accounting understanding, learning behavior has no effect. on understanding of accounting through intellectual intelligence, and interest in learning has a significant effect on understanding of accounting through intellectual intelligence.